Differential effects of IL-6 blockade tocilizumab and TNF inhibitors on angiogenesis in synovial tissues from patients with rheumatoid arthritis. Issue 5 (3rd September 2017) - Hirohata, Shunsei; Abe, Asami; Murasawa, Akira; Kanamono, Toshihisa; Tomita, Tetsuya; Yoshikawa, Hideki
Abstract: Objective: To compare the influences of tocilizumab (TCZ) and TNF inhibitors (TNFi) on the angiogenesis in synovial tissues of rheumatoid arthritis (RA). Methods: Synovial tissues were obtained during joint operations from 13 RA patients treated with TCZ for at least 4 months with or without previous use of TNFi, from 13 RA patients with TNFi alone and from 10 RA patients with only conventional synthetic DMARDs (csDMARDs). Synovial tissues were evaluated by hematoxylin and eosin stain as well as by immunohistological staining with anti-CD31 in which the microvessel densities (MVD) were quantitated. Synovial histopathology was scored for various components. Results: The most remarkable change in the synovium with TCZ was reduced angiogenesis as well as degeneration of lining layers irrespective of the previous use of TNFi. Thus, MVD in patients treated with TCZ with or without previous TNFi were significantly decreased compared with those in patients with TNFi alone or with csDMARDs. Moreover, MVD was significantly correlated with lining layer proliferation, but not with synovial stromal proliferation or inflammatory changes. Conclusions: These results demonstrated that inhibition of angiogenesis is a unique action of TCZ. Moreover, the data also suggest that lining layers proliferation might be closely associated with angiogenesis.